Comparative evaluation of physico-morphological attributes and freezability of semen of Gir cattle (Bos indicus) and Jafarabadi buffalo (Bubalus bubalis) bulls - SHELKE, VINAY B; DHAMI, A J (The Indian Journal of Animal Sciences, 2014)
Semen ejaculates (99; 9 per bulls) obtained at 3-days interval from 6 Gir and 5 lafarabadi bulls; aged 4-7 years and of different freezability grades (good and poor); were evaluated for various physico-morphological attributes, freezability, cold shock resistance and their interrelationships. The mean values in Gir and lafara0.01 and 6.66 ± 0.02, mass activity 2.96 ± 0.14 and 2.23 ± 0.15 (P